Surface modification of calcium phosphate scaffolds with antimicrobial agents for bone tissue engineering - Barbosa, Lucas (2023)
This chapter provides an overview about some innovative strategies to functionalize calcium phosphate scaffolds’ surfaces by using antimicrobial agents to combat osteomyelitis. The scaffolds can be obtained by different techniques and must fulfill some requirements, including open and interconnected porosity, mechanical and biological properties, and biomaterial requirements. Also, special attention was given to understanding the mechanism of action of antimicrobial agents (antibiotics, nanoparticles (NPs), and photosensitizers (PS)) that is essential to enhance the development of efficient antimicrobial scaffolds. Finally, this chapter reports on recent results obtained by our group regarding the development of β-tricalcium phosphate (β-TCP) scaffolds with antibacterial properties afforded by the incorporation of silver nanoparticles and methylene blue.